Assessing the Vulnerability of Armenian Temporary Labor Migrants during the COVID-19 Pandemic - Honorati, Maddalena; Yi, Soonhwa; Choi, Thelma (World Bank, Washington, DC, 2020)
This paper attempts to assess the vulnerability of Armenian temporary international labor migrants and their families to the labor market challenges posed by the Coronavirus (COVID-19) outbreak. The authors estimate that about fifty percent of temporary labor migrants might have been unable to leave for Russia owing to travel restrictions. Many Armenian migrants in Russia are likely to lose jobs because of some halts in construction activities. Prospective migrants who were unable to leave Armenia are more likely to be jobless based on the employment status they had prior to departing for Russia. This would result in reducing remittances and exposing remittance-dependent households to precarious situations. Targeted policies to address this new vulnerable group are called for.